Kingdom of Morocco - Recent Economic Development in Infrastructure : Water Supply and Sanitation Sector - World Bank (Washington, DC, 2013)
As part of its agenda to promote economic growth, improve access to services, and control environmental degradation, the Government of Morocco (GOM) has set the following objectives: increase access to potable urban water to the population to 100 percent by year 2008; increase access to potable rural water to 92 percent by year 2007; in regard to pollution control abatement, increase treatment of wastewater loads from 7 percent in 2004 to 60 percent by 2010, and to 80 percent by 2015. This report is a diagnostic of infrastructure needs and services in Morocco's water supply and sanitation sector (" the water sector ") in both urban and rural areas. It provides an overview of the economic context, and of the sector's organization, institutional and regulatory framework, performance, services to the poor, and investment needs. Options and recommendations for reform are the subject of ongoing policy dialogue with the Government of Morocco, and will be presented in detail in separate documents due for later publication.